2020
DOI: 10.1159/000505232
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Limbic Encephalitis Associated with Anti-CV2/CRMP5 Antibodies Secondary to Thymoma in an Adolescent

Abstract: Paraneoplastic neurological syndromes (PNS) associated with anti-CV2/CRMP5 antibodies are rare in the literature. Various clinical manifestations can occur including paraneoplastic limbic encephalitis (PLE). Thymoma is one of the rare causes that can be associated with this syndrome. It has not been reported in the literature in children or adolescents to the best of our knowledge. We report a case of PLE in a 19-year-old male patient secondary to thymoma that was diagnosed after 5 years of onset. Anti-CV2/CRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
0
11
0
4
Order By: Relevance
“…Anti-CRMP5-associated paraneoplastic encephalitis is rare. Most cases are associated with SCLC, occurring in 5% of patients 8. Although the patient presented pleocytosis, he had no symptoms suggestive of encephalitis.…”
Section: Discussionmentioning
confidence: 85%
“…Anti-CRMP5-associated paraneoplastic encephalitis is rare. Most cases are associated with SCLC, occurring in 5% of patients 8. Although the patient presented pleocytosis, he had no symptoms suggestive of encephalitis.…”
Section: Discussionmentioning
confidence: 85%
“…Presently, even though the anti-CRMP 5 antibodies are rare among the intracellular antibody spectrum, it has a documented oncological association of 75% toward SCLC and 15% toward thymoma, with patients between 30 and 50 years old, being equally found in men and women. However, a 2020 study has reported the correlation of the autoantibody with thymoma 19 . In a clinical perspective based on the largest conducted study regarding anti-CRMP 5 antibody detection, it was reported that the primary psychiatric manifestation was nonspecified personality change (11%), followed by depression (9%) and psychosis (4%) 32 …”
Section: Resultsmentioning
confidence: 99%
“…The CRMP5 antibody is an intracellular antibody that is almost always paraneoplastic and most commonly seen in SCLC (about 75% of cases), again not with other types of lung cancer [ 14 , 15 ]. Clinically, CRMP5 is frequently associated with painful peripheral neuropathies and cerebellar ataxia.…”
Section: Discussionmentioning
confidence: 99%